Reverse logistics strategic antinomies: The case of the automotive sector - George Blanas; Stelios Koukoumialos; Stamatia Kylindri (International Journal of Business Science & Applied Management (IJBSAM), 2012)
Legislation plays a major role in the automobile manufacturing sector. The European legislation has a prominent international role in this respect. We examine the impact of the European Parliament, Council (2000) Directive 2000/53/EC on the EU automobile sector reverse logistics activities in the light of the Extended Producer Responsibility (EPR) principle. We argue that there is an antinomy in the application of the Directive that is supposed to support an EPR strategy. The antinomy is expressed by [1] the absence of the necessary capabilities of Producer Responsibility Organizations (PROs) to advance to higher reverse logistics activities like remanufacturing [2] an indefinite delay of the possibility for transformation of the current forward chain manufacturing model, [3] a stability in the strategic group formation of the European automobile manufacturing sector that prevents the further diffusion of manufacturing and remanufacturing capabilities within EU with profound positive economic impacts in favour of the industrialized countries with a strong automotive manufacturing sector and negative impacts to less industrialized countries. We also argue that the proper application of the EPR strategy is in favour of established EU manufacturers and can act as a barrier to entry for non-European firms.
Keywords: 650; automotive sector; reverse logistics; strategy; legislation; EC Directive; EPR